2016
DOI: 10.1248/bpb.b16-00418
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Risk Factors for Linezolid-Associated Hyponatremia in Japanese Patients

Abstract: Linezolid is an oxazolidinone antibiotic against Gram-positive bacteria. Although thrombocytopenia is a major adverse effect of linezolid, hyponatremia also often develops after linezolid administration. This study examined the frequency of hyponatremia that developed during linezolid treatment and identified its risk factors. In this retrospective, single-center, observational cohort study, 61 hospitalized patients treated with linezolid between January 2013 and January 2015 were analyzed. Hyponatremia was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…Consequently, close monitoring of PLT count and early switch to other agents when PLT count starts to decrease may have been done more frequently for patients in our study. On the other hand, the incidence of LZD‐induced hyponatraemia was 17.5%, which is almost the same as that in our previous research 18 . By excluding patients receiving treatment for less than one week, the incidence was expected to increase, but this was not observed.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Consequently, close monitoring of PLT count and early switch to other agents when PLT count starts to decrease may have been done more frequently for patients in our study. On the other hand, the incidence of LZD‐induced hyponatraemia was 17.5%, which is almost the same as that in our previous research 18 . By excluding patients receiving treatment for less than one week, the incidence was expected to increase, but this was not observed.…”
Section: Discussionsupporting
confidence: 80%
“…The risk factors related to hyponatraemia and/or thrombocytopenia were analysed by univariate and multiple logistic regression, using the following as independent variables (data before LZD initiation): administration period, dose per body weight, age, PLT count, ALB, CRP, Na and Ccr. We selected the above factors as covariates in univariate analysis for the following reasons: administration period, 7‐9 dose per body weight, 9,10 ALB 9 and Ccr 7‐12 are known risk factor for LZD‐induced thrombocytopenia; CRP is a known risk factor for hyponatraemia 18 ; older people are more susceptible to develop hyponatraemia; PLT level is the parameter of thrombocytopenia (PLT); and Na level is the parameter of hyponatraemia. In common practice, variables with P < .25 in univariate analysis are included for analysis in multivariate models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 antibiotics such as fluoroquinolones, bactrim, linezolid, and aminoglycoside are now being reported much more often to cause hyponatremia primarily with a picture compatible with SIADH. [3][4][5][6] While most of the drugs can cause hyponatremia by inappropriately increasing the ADH levels, antibiotics on the rule hand still not well defined. Similar to our patient, this has often occurred in elderly patients, frequently with multiple other factors that helped in the development of hyponatremia.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, older patients are more susceptible to developing hyponatremia due to (i) impaired water excretory capacity resulting from a reduced glomerular filtration rate, (ii) reduced total body water content and (iii) the more frequent occurrence of SIADH due to underlying diseases and medications . Linezolid is an antibiotic that has been described to cause mild hyponatremia in up to 18% in a small cohort of patients; however, the mechanism is not clear, and severe hyponatremia (≤128 mEq/L) is extremely rare (1.6% of patients) and is generally not considered to be associated with SIADH . Baik et al reported the case of a patient who developed hyponatremia during treatment with linezolid with findings suggestive of SIADH implying that either linezolid directly stimulated the production of ADH or that ADH was produced due to a drug to drug interaction of linezolid with buspirone that the patient was also receiving …”
Section: Details Of the Casementioning
confidence: 99%